Compléments des programmes de géographie de l’élémentaire : valait-il mieux jamais que si tard ? - Xavier Leroux (Cybergeo, 2012)
The article deals with developments in the teaching of geography in France, that have been suggested in the 2012, 5th January official instructions that complete the 2008 curricula. Given the risk that these references proposed to teachers become definitive, we have underlined their principal negative aspects.